Evaluación Económica y su incidencia en la Gestión Administrativa FInanciera en la compañía de transporte pesado Rutas Fronterizas RIo Amazonas S.A. Fronteramaz, ubicada en el cantón Joya de los Sachas, provincia de Orellana en el periodo 2017-2018 - Maigua Lamingo, María Sara (2019)
The present research project was developed in the company of heavy border routes Rio Amazonas SA Fronteramaz with the purpose of making an economic evaluation and its incidence in the financial administrative management, based on the research topic, ECONOMIC EVALUATION AND ITS INCIDENCE IN THE FINANCIAL ADMINISTRATIVE MANAGEMENT OF THE HEAVY TRANSPORTATION COMPANY BORDER ROUTES RIO AMAZONAS SA FRONTERAMAZ, LOCATED IN THE CANTON JOYA DE LOS SACHAS, ORELLANA PROVINCE IN THE 2017-2018 PERIOD, so that the main problem that afflicts the company, this being how the economic evaluation affects the incidence of the financial management of the company, for which a survey and interview format was made, which allowed to know that the company has a scarce economic evaluation and its impact on administrative financial management, for which reason it was raised as Objective To formulate a methodological guide on economic evaluation for its impact on financial management. For which also theoretical framework was made being very important because it allows to have the definitions of all the research which contributes to a better understanding and development of the work. The investigation also has a legal framework because the laws that govern the company in the development of the activities are detailed, in the development of this investigation the following methods were also used, Analytical Method, which allowed us to perform an analysis and interpretation of the results obtained through the application of surveys and interviews, deductive and inductive method, this method allowed us to analyze the problem of the investigation from its generalities to its particularities and vice versa and the historical method being that which was used for the realization of the antecedents and base the research bibliographically. Keywords: Economic evaluation, incidence, financial management, company, activities, methodological guide.